Mimarinin kıvamı: Dikiş figürasyonu ve şehirde yürüyüş inşaları üzerinden bir araştırma - Uysal, Hatice Işıl (Lisansüstü Eğitim Enstitüsü, 2021)
Maddi bir olgu olan şehir farklı kuvvetlerin etkisiyle çok farklı şekillerde biçimlenmekte ve yaşanmaktadır. Biçimlendirerek ve deneyimleyerek şehirde görünür hale gelen görme biçimlerinin etkinliği olmaktadır. Şehri insan kendi görme biçimiyle inşa etmekte; mesafe ve ayrıklık ile karakterize olan hakim özne konumlarına bağlı olarak insani anlamlar üreten bu bakış kendi nesnelerini yaratmaktadır. Otoyollar, sokaklar, kıyılar, farklı kullanımlardaki yapılar, parklar ve diğer çevresel müdahaleler yukarıdan bakış ile sokak kotunda olmanın tüm ara seviyelerinin okunaklı nesnellikleridir. Yürüyüş şehirde beden seviyesinde, insan ve insan-dışı her şeyle aynı düzlemde gerçekleşen bir eylem olarak yakın ilişki ve çevresel bağlar kurmaktadır. Yukarıdan bakışla bir uydu haritasında görünen şey eğer bir yüzeyse, yürüyüş yüzeyin derinliğindeki maddenin bir hareketi olmaktadır. Tez kapsamında yürüyüşlerin kurduğu yakın ilişkilerin ve bağların detaylarına bakmak ve inceltmek üzere dikiş bir imge, yüzeyin derinliğine temas ederek maddeyle ilişkilenen ve gömülü olanı çözen bedenlenen bir kavram olarak ele alınmaktadır. Dikişin özellikleri üzerinden bedensel bağ dokudan başlamak üzere bedensellikler ve mimariler tartışılmaktadır. Tez sürecinde İstanbul'da bir seri yürüyüş gerçekleştirilmiştir. Yukarıdan bakışla görülen yüzeyler kesik, yırtık, parça olmaları yönünden değerlendirilerek bunların arasından geçen, dik yön rotaları olarak belirlenen ve çizilen hatlarda yürünmüş, yürüyüşlerin dik yönün ayrıklıklarını diktiği imgelemiyle hareket edilmiştir. Bu tez özne ve nesne oluşun aşırılaştığı, inceldiği ve etkileşimler üzerinden betimlendiği bir rotayı takip etmekte, görme biçimlerini ve failliği sorunsallaştırarak mimariyi yüzeyin derinliğindeki maddede oluşan bir ilişkiler seti olarak tartışmaktadır. Bu tartışmalar tez kapsamında yapılan yürüyüşlerdeki etkileşimlerin irdelenmesiyle yapılmaktadır. Yürümenin dikmek olduğu düşüncesiyle dikiş; katılımcıları iğne, iplik ve kumaş olan, katılımcıların birbirini ziyaretiyle gerçekleşen, kesik, delik ve yırtıkların onarıldığı, yeni birleşimlerin oluştuğu ilişkisel, sağaltıcı ve birleştiren ancak dönüştürmeyen bir imgedir. Bu imgede iğne uğrayan, kumaşta delik açarak iplikle izler bırakan ve ayrılan, ip kumaşı kat eden ve birleştiren, kumaş ise birçok ipliğin birbirinden geçmesiyle oluşan ve iğne ile ipin tüm ziyaretlerine açık olan katılımcılardır. Birbirine uğrama ve ayrılmanın yaşanmasıyla gerçekleşen bu ziyarette ipliğin kumaşta yol almasından dolayı mekânzamansal birleşimler oluşmakta, katılımcıların birbirini ziyaretiyle maddi bağlar kurulmaktadır. Dik yön; akışın tersine veya akışı geçen bir yoldur. Bu yolu açmak veya bu yolda hareket etmekle, engelli, engebeli, parçalı, ayrık, keskin, çoklu ve sıcak bölgelerden geçilmektedir. Şehirde dik yönler bu çalışmada planlanmış ancak zorlayıcı olan hatlardır, çünkü şehirde var olan akışların dikine geçmekte, bunu yaparken ayrıklığı oluşturan görme biçimini bağlantısallığa doğru açılmaya zorlamaktadır. Ziyaretçi, sürekli, sağaltıcı, bağlayıcı ve sakin bir imge olarak dikişin sıcak bir dik yönle buluştuğu yer beden seviyesidir. Beden gevşek bir bedenlenme, beden seviyesi ise etkileşimli ve çok-anlamlı bir bölge olarak ele alınmaktadır. Çalışma beden seviyesinden dikiş hayaliyle başlayarak gezintiye çıkan ve şehir yüzeylerine yüzü izleyene çevrilmemiş yönlerinden yaklaşan bakış etrafında şekillenmektedir. Dikişi imgeleyerek oluşan figürasyonlarla, metinler, görüntüler ve yerler arasında yürüyerek kurulan çalışmanın yöntemi (posthümanist) fenomenolojik yaklaşımla çerçevelenmektedir. Tez metni dünyada endüstriyel orman ile kutsal orman arasındaki dramatik farkın, bu farkı oluşturan yaklaşım ve yaşantının üzerine düşünülmesiyle başlar. Endüstriyel orman imgesi ormanın kesilmek üzere var olduğu düşüncesi, insanın merkeziyeti ve diğer şeylerin onun için malzeme oluşuyla oluşmaktadır. Bu düşünüşten yola çıkarak çevreyi beden seviyesinden insan-merkezli olmayan bir bakışla görebilmek, insan yapımı olanı, mimari inşayı, insana bağlı ve insandan türeyen anlam katmanlarını, maddeye bakışı ve algılamayı sorunsallaştırmaktadır. Bu sorunsallaştırma ile kıvamlı mimari tezin maddesel etkileşimler, hareketler ve anlamları irdeleyen kuramsal tartışmasının kapsamını ifade etmekte, insan ve insan-olmayan maddenin iç içe geçmiş ağı ontolojik zemin olarak alınarak maddesel bütünlüğün içerisinden yüzey ilişkilerine yaklaşılmakta ve mimari fenomenoloji alanında hareket edilmektedir. Mimari fenomenoloji şeylerin kendisini gösterdiği şekilde görülmesi ve gösterilmesi ile hareket halinde, deneyime bağlı olarak ve yaşayarak inşa olan mimariyi öne sürmektedir. Bu alanda biri yüzeyin ardının hayali, görünür olanın anlamlarının oluşma süreci ve bu oluşun katılımcılarının, gömülü olanın nasıl bir bedenlenme olduğunun irdelenmesiyle, diğeri bedensel özellikler olan zamansallık ve mekânsallık üzerinden gerçekleşen algılamaya bağlı inşa ve bedenlenmenin maddiliği ile çevçevelenen iki yaklaşımın söz konusu olduğu ve bu iki yaklaşımın zaman zaman birlikte ele alındığı izlenmektedir. Mimari fenomenoloji bu bağlamda madde, anlam ve inşanın algılamaya bağlı olarak irdelendiği kuramsal pratik bir alan olmaktadır. Öte yandan fenomenolojik betimlemelerin insan-madde ile nesne arasında oluşan deneyim anlatıları insandan kaynaklanan tek yönlü anlamları içerdiği için betimlemeler problematize edilmekte ve içerisindeki maddesel hareketlerin tekrar değerlendirilmesine ihtiyaç duyulmaktadır. Tez kapsamında merkezileşen bakış filtresi kaldırıldığında oluşacak ilişkilerin iç içeliğinin görülebilmesi ile anlamların çokluğu konu edilmekte ve ontolojik olarak ortak bir zeminden, maddeler arası, gevşek bir bedenlenme içerisinden ancak beden seviyesinde kalarak çevreye bakılmaktadır. Tanıdık olanın içinden geçip gitmek yüzeyleri maddenin bir işlevi olarak görmenin ve ilişkileri insani bağlardan fazlasını içeren karışımlara doğru genişletmenin yöntemi olmaktadır. Yeryüzüne koruyucu ve sevecen bir örtü seren yürüyüşler, dikiş imgelemiyle birlikte yüzeylerin bağlarının bakım ve sağaltımı için aracı olmakta, yüzeylerle ilgilenmek ise hem kendine hem de çevreye sağaltıcı bir şekilde temas etmeyi sağlamaktadır. Şehrin tüm failleri kendi yapılarında ilişkiler üreterek kıvamı değişen bir karışım yaratırken, mimarinin bu karışımın içerisinde ne olduğunu tartışmak, genişleyen bir etik düzlemde dünyanın ihtiyaç duyduğu farkındalık ve duyarlılık için bir adım olarak görülmektedir.

As a material phenomenon, the city is formed and lived in with very different ways under the influence of myriad forces. People, by being one of these forces, build the city with their own way of seeing. This view, which is characterized by distance and separation, is dependent on dominant subject positions, and produces human-derived meanings while creating its own cultural objects. Highways, streets, shores, buildings and structures of different use, parks and other environmental interventions are all readable objects that are visible through all the intermediate levels between street and top views. Walking, as an action at the body level, takes place on the same ground where the humans and non-humans meet. It creates close relationships and environmental bonds. If what appears on a satellite map viewed from above is a surface, the walk is a movement of matter at the depth of this surface. In the scope of the thesis, stitching is taken as an image, an embodied concept in order to examine and delineate the details of the close relationships and bonds created by the walks. By starting from the bodily connective tissue, embodiment and architectures are discussed through the characteristics of stitching. During the thesis process, a series of walks were held in Istanbul. The surfaces seen on satellite maps were evaluated in terms of being cut, torn, and fragmented, and the lines passing through them, which were determined and drawn as orthogonal routes, were walked with the imagination of stitching the discreteness of the orthogonal directions. This thesis follows a route where the subject and object become extreme and delineated through interactions, problematizes the forms of seeing and agency, and discusses architecture as a set of relations formed in the matter at the depth of the surface. These discussions are made by examining the interactions in the walks made within the scope of the thesis. While thinking as walking is stitching, stitching is a healing, intertwining and connective but non-transformative image, whose participants are needle, thread and fabric. It is realized through the visits of the participants. By these visits, cuts, holes and tears are repaired, new combinations are formed. In this image, the needle is the participant who visits, makes holes, and exits the fabric while leaving its traces as threads; the thread is the one who wanders through the fabric and joins pieces; the fabric is the participant who is formed by the entanglement of many threads and is open to all visits of the needle and thread. Being a temporal act due to the movement of the thread through the fabric, the narrative of stitching is felt as a viscosity because it is spatiotemporal, and material bonds are established by the visits of the participants. The orthogon is a direction that is cross-flowing, erratic, uneven, and challenging. It is a fragmented, cut, striated, variable, multiple and an entropic region. The orthogonal directions of the city are the lines that are drawn in this thesis, but they are challenging because they cross perpendicular to the existing flows in the city, forcing the way of seeing that creates separations to open towards connectivity. Within the scope of this thesis, the place where the healing, intertwining, connective and peaceful image of stitching meets an entropic and challenging orthogonal direction is the body level. The work starts with imagining the body stitching the world. It is shaped around a gaze that goes for a walk and comes close to city surfaces through orthogonal directions. By imagining walking as stitching, the needle passes through the surfaces of the city and gets connected with the matter that is embedded at the depths and beyond the surfaces. By this deep contact of the needle, one gets in a close relation with the matter of the city on orthogonal directions while dissolving the surfaces. While the embodied image of the stitch provides a way of seeing and relating with the environment, it opens up a space for discussions about the construction of relations that are based on seeing and experiencing. The methodology of this work, which is constructed by setting off and walking with the image of stitching and visiting texts, images, and places with a figuration that is embodied by imagining stitching, is framed by a (posthumanist) phenomenological approach. Based on his personal experience, Wade Davis (2015) tells us about two differentiating forests derived from two different ways of seeing: the forest that exists to be cut down and the forest as sacred land. The dramatic difference between the industrial and sacred forest is grounded by different operational ways of living: the forest that is about to be cut down results from the operations of the conceptual human who is constructed as a discrete entity and located at the very center of things. At the center, a materialization of things begins, the matter becomes material, topological relationships transform into central geometric projections. When the human in the center shifts and the center does not exist anymore, we begin to see the matter-being of the material, the intertwinement of a forest, trees, air, animals, inanimate beings, and the people who belong to this intra-active bond. When the tree as material comes to be seen as an embodiment in the ecology of things, humans and the forest become a viscous mixture, and for the human, the forest becomes a meaning from its own connective tissue. Touching the world becomes touching oneself. In this context, seeing the environment from the body level with a non-anthropocentric perspective problematizes the human-made thing, the cultural object, architectural construction, human-related and human-derived layers of meaning, understanding of matter, and perception by means of discreteness. Depending on this problematization, viscous architecture frames and amplifies the theoretical discussion of this work. It expresses the intra-active matter as the ground and delineates the movements and meanings as the functions of this ground. This work would position the phenomenology of architecture by being close to surface relations at the body level, embodied from a new materialist point of view. Architecture is the construction of surface relations based on identification. Perez-Gomez (1998) describes architecture as creating an order that is resonant with the body itself. Alternatively, the architectural design process takes place by translating the worlds of lines, images, substances, surfaces, and atmospheres to each other. It is the process of embedment, embodiment, intertwining, juxtaposing, construction (deconstruction and reconstruction), and emergence. Therefore, the world of architectural design is a mixture of lines and matter, while architectural construction is a movement that takes place in this mixture, entangling the linealities and the materialities. In this movement, the anthropocentric view, which materializes the matter and sees it as a single meaning, is located at the body level. Taking it for a walk and exploring the possibilities of the thing to project itself without a centralized perspective are the ways to dissolve this view. The phenomenology of architecture encompasses both cases by proposing that architecture is constructed in motion, through the experiences or by seeing and showing things as they manifest themselves. In this field, there are two intertwining approaches. One is formed by the imaginary below the surface while examining the becoming process of the meanings through the visible, the participants of this becoming, and embodiment of the embedded through the manifest. The other is based on bodily properties of spatiotemporality that create constructions through perceiving and the materiality of the image. In this context, the phenomenology of architecture is a field of theoretical practice where matter, meaning, and construction are examined re perception. Conversely, since the experience narratives of phenomenological descriptions between human-matter and object contain one-sided meanings derived from subjectivities, the descriptions are problematized in terms of reproducing dualities created by a conceptual human. The bodies are read as embodiments, and the matter that is embedded in the narratives is examined and amplified. Within the scope of this work, entangled relationships immanent to the vibrant matter and the myriad meanings that become imaginable after removing the anthropocentric gaze filter are discussed. By problematizing the central position and seeing that it is constructed as a variant of that specific position, the environment is explored while being on the body level. The body is conceived as (in Neimanis' terms, 2017) a dispersed lived embodiment. Imagining the diversity and multiple positions of the body as a lived embodiment creates posthuman bonds, and seeing the environment through these bonds raises questions about the connectedness of architecture. A field emerges as posthuman bonds in viscous mixtures, and architecture becomes myriad meanings of different identifications. While working on the possibility of constructing a viscous architecture only by being at the body level and perceiving, the entanglement of the ties is pursued. Discussing what architecture is in the viscous mixture is evaluated as a step towards creating an awareness and sensitivity in an expanded ethical ground that the world needs. This work moves in the expanding field of architecture and takes the intertwined network of human and non-human matter as the ontological basis, which Braidotti (2019) calls, Zoe. The content of the work is constructed by visiting the works of various artists, concepts and imaginations of authors, the images of the walks, photographs taken during the walks, post-walk drawings, the collaboration of the surfaces, and their association with the stitching image. On the path of this work, Gibson, Norberg-Schulz, Perez-Gomez, and Careri describe the environment and surfaces, Derrida, Lynn, Virilio, Merleau-Ponty, Heidegger, Ingold, and Dormor delineate the forms of relationships. Then, with her artwork, "A Needle Woman," Kimsooja inspires about being a needle and imagining the thread. Next, Zevi starts to describe how to see architecture, and after Zevi, Holl continues. Finally, Latour leads to a bifurcated path that only unfolds by looking in a myopic way. The narrative of the path is written and discussed in five chapters. The Introduction chapter is both an overview of this thesis's field and the specification of the departure point by describing the methodology. By being the conceptual frame of this thesis, the second chapter, Walking and Stitching, starts with the body level, examining stitching at this level, and ends by exploring walking through the projection of stitching. The third and fourth chapters are the fieldworks examined through stitching figuration. The third chapter Seeing Architecture in the Viscous City is the theoretical fieldwork that is constructed by imagining the fabric and the needle that passes through the material. Fabric becomes the viscous city where all of the formations of matter through movement and speed are visible. Seeing architecture at the body level starts with Zevi (2015) as he indicates seeing architecture is like observing a sculpture; architecture is to be seen while it is walked around and lived inside. "Sculpture in the Expanded Field" is the field where architecture is also expanded. Architectures through phenomenological approaches and their expanded versions through being examined in a new materialist way of seeing frame the discussions of this part. The fourth chapter is the practice-based part of this work. It begins with indicating how the city is experienced as orthogonality and continues with the narratives derived from the walks that were intended as stitching routes. The last chapter is an overview from the end of the path. The background of the work that is constituted of walks is included in the appendices. According to Solnit (2016), "like threads moving through the fabric each walk moves through space and stitches it into being a continuous experience." Wade Davis states that "the indigenous communities of Sierra Nevada described their periodic walks as threads, with the imagining of weaving a protective mantle over the earth." Throughout this exploration, the image of stitching suggests the quality and intention of establishing relationships and the healing of damaged bonds. Walking as stitching leads into a posthuman world and manifests the possibility of healing the material bonds of the surfaces. This work walks with the fragile image of stitching through the orthogonal direction of the city and sees the city as a viscosity. It enters into a posthuman world with a body that is a dispersed embodiment. This position, somewhere in the vibrant matter, re-reads the texts that examine meaning, making, and architectures with a phenomenological approach. Re-reading becomes a way to extend these approaches into the mixture and entanglement of the human and non-human. Graduating from the familiar becomes the methodology to see the surfaces as a function of the matter. Taking care of the surfaces appears to be a healing touch both for oneself and to the environment.
Viscosity of architecture: A research through stitching figuration and walking constructions in the city
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Fenomenoloji; Phenomenology; Mimarlık; Architecture; Yaratıcı imgelem; Creative imagination